The primary market in housing and apartment developments in poland’s six largest cities over the course of the COVID-19 pandemic - Rynio, Dorota (Rynek pierwotny nieruchomości mieszkaniowych i domów w sześciu największych miastach w Polsce w dobie pandemii COVID-19, 2021)
The research problem examined in this paper pertains to the situation on the primary market in apartment units and detached housing units over the course of the COVID-19 pandemic, namely between October 2020 and September 2021. The main research objective was to present current trends on the primary market in apartment units and detached housing units in the radically specific context of the present pandemic threat. The study was designed to examine local markets in real estate in Poland’s six largest cities. The fundamental research question was formulated as follows: what trends could be observed in the primary market of apartment units and detached housing units in response to the ongoing pandemic threat, and what directions of development can be seen as those most favoured by the market in question? In an attempt to provide a complete picture of the studied trends, a supplementary question was posed as follows: what are the most important determinants of the market’s development in the studied pandemic context? The research questions were approached by means of analytical evaluations of fluctuations in housing and apartment prices by city, complete with analyses of availability, sales volumes and supply of new units. The study employed the following research methods: literature studies, trend analysis, observation, and rudimentary statistical methods.
Biblioteka Regionalisty, 2021, Nr 21, s. 160-169
Keywords: primary market; secondary market; apartments and houses; Poland's largest cities; rynek pierwotny; rynek wtórny; mieszkania i domy; największe miasta w Polsce